2 - Le fonds d’équité au Sénégal : analyse des mécanismes de la couverture maladie des indigents et de ses perspectives pour la couverture maladie universelle - Ndiaye, Sara (Africa Development, 2017)
In June 2010, an equity Fund has been initiated in 4 regions of Senegal for a period of 36 months. The services started in 2012. The recipients are the most deprived persons characterized by a vulnerability to diseases: pregnant women, children under 5 years old, people with disabilities and the elderly people. Their medical care is ensured through health mutuals in accordance on the basis of agreements with health facilities. This is usually a 60 percent to 80 percent coverage of primary care and packages for referral care. The supplement is covered by equity fund. For its implementation, several actors have overseen the process to ensure the principles of participation, equity and compliance to the procedures manual. The mutualist societies and the social welfare services constituted the spearheads of the identification and validation of recipients lists. An agreement was subsequently adopted between the Universal Health Coverage Support Unit (CACMU) and health mutuals. This article aims to promote action research on the experiences of health protection in a context of economic poverty. It is based on a literature review and a participant observation. Thus, the study was able to prove that the mutualist approach is relevant for universal health coverage. However, the innovations developed by community health mutuals are few capitalized in the public policies of social protection. Moreover, the key milestones presented for the promotion of universal health coverage include: the diversification of funding (State, cooperative, local authorities, businesses, employees), the coverage of major risks to make more attractive the community health mutuals and the improvement of management methods of the mutualist structures.